Public Debt and Exchange Rate Stability in Nigeria: An Empirical Analysis - Nwikina, Christian Gbarawae; Naakuu, Joseph Kpobari (NIU Journal of Social Sciences; Vol 9 No 3 (2023): NIU Journal of Social Sciences, Vol. 9 No. 3, September 2023DO - 10.58709/niujss.v9i3.1708, 2023)
This study examined public debt and its effect on exchange rate stability in Nigeria from 1980 to 2019. The data were subjected to statistical analysis using vector autoregression model. Using data on external and domestic debt servicing ratio to total debt stock, the findings showed no significant relationship between public debt and exchange rate stability in Nigeria within the period, likewise for ratio of external debt servicing to total external debt stock and exchange rate. Finally, domestic debt servicing had no significant relationship with exchange rate.  The study concluded that as Nigeria increases external debt servicing, domestic prices increases and this also affects exchange negatively. It is recommended that concerted effort be intensified towards decreasing the level of external debt profile of Nigeria which will invariably decrease external debt servicing. Also, government should intensify revenue drive through exploring other viable sources that do not have repayment plan rather than relying on augmenting yearly budget through public debt accumulation. Keywords: Public Debt, Exchange Rate, Economic Stability, External Debt Servicing Ratio, Nigeria Economy.